2015
DOI: 10.1055/s-0035-1564726
|View full text |Cite
|
Sign up to set email alerts
|

Time Interval between Trauma and Arthroscopic Meniscal Repair Has No Influence on Clinical Survival

Abstract: Arthroscopic meniscal repair is the gold standard for longitudinal peripheral meniscal tears. The time interval between trauma and meniscal repair remains controversial. The aim of this study was to evaluate failure rates and clinical outcome of arthroscopic meniscal repair in relation to chronicity of injury. A total of 238 meniscal repairs were performed in 234 patients. Anterior cruciate ligament (ACL) was reconstructed in almost all ACL-deficient knees (130 out of 133). Time interval between injury and rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…Failure of meniscal repair was compared between patients who underwent simultaneous or delayed (>6 weeks) ACLR in a cohort study by Majeed et al 36 Meniscal repair failed in 14.5% of patients who underwent concomitant ACLR (or within 6 weeks) and in 27% of patients who underwent delayed reconstruction ( P < .05). Similar results were reported by Gallacher et al 21 and several other investigators, 5 , 26 , 42 , 52 although in these studies, the results were not statistically significant or no statistical analysis was reported. Only 1 study reported no detrimental effect of ACL deficiency on survival of meniscal repair, although no specific data were provided.…”
Section: Resultssupporting
confidence: 86%
“…Failure of meniscal repair was compared between patients who underwent simultaneous or delayed (>6 weeks) ACLR in a cohort study by Majeed et al 36 Meniscal repair failed in 14.5% of patients who underwent concomitant ACLR (or within 6 weeks) and in 27% of patients who underwent delayed reconstruction ( P < .05). Similar results were reported by Gallacher et al 21 and several other investigators, 5 , 26 , 42 , 52 although in these studies, the results were not statistically significant or no statistical analysis was reported. Only 1 study reported no detrimental effect of ACL deficiency on survival of meniscal repair, although no specific data were provided.…”
Section: Resultssupporting
confidence: 86%
“…The time between injury and primary repair varied among the patients, but a study by Espejo‐Reina et al [10] demonstrated that there is a good clinical healing rate of 83% for meniscal repairs 2–60 months after injury. van der Wal et al [30] found no significant difference in clinical outcomes in meniscal repairs < 2 weeks or > 12 weeks after injury. Other studies [14, 31] have shown better clinical outcomes in early repairs within 3–6 months after injury.…”
Section: Discussionmentioning
confidence: 99%
“…Failure rates in older patients have been shown to be similar to those quoted for younger patients and good clinical outcomes can be obtained,30,31 but care should be taken to determine whether tears in older populations are degenerative or traumatic in nature as this may speak to the quality of meniscal tissue present and its suitability for repair 12. Finally, while some studies have demonstrated improved outcomes with earlier repair,32,33 chronicity is not necessarily prohibitive in an otherwise indicated meniscal repair 34. Rather, as with the other factors listed above, tissue quality present at the time of repair is the most important.…”
Section: Indicationsmentioning
confidence: 95%
“…12 Finally, while some studies have demonstrated improved outcomes with earlier repair, 32,33 chronicity is not necessarily prohibitive in an otherwise indicated meniscal repair. 34 Rather, as with the other factors listed above, tissue quality present at the time of repair is the most important.…”
Section: Indicationsmentioning
confidence: 99%